The Influence of Japanese Work Cultures on Malaysian Foodservice Employees' Work Stress and Their Turnover Intention - Kamal, Mohd Fairuz Mustaffa; Zahari, Mohd Salehuddin Mohd; Hanafiah, Mohd Hafiz; Ariffin, Nurul Wahidah Mohammad (The South East Asian Journal of Management, 2020)
Research Aims - This study investigates the influence of Japanese work cultures on Malaysian foodservice employees’ work stress and their turnover intention. Design/methodology/approach - A total of 381 respondents participated in this study, and the research data was validated prior to the empirical assessment. Research Findings - The results of this study signify that the Japanese work culture amplifies workers disorientation, stress and turnover intention. Besides, thru hierarchical regression, workplace stress was found to mediate the relationship between Japanese work culture and employee turnover intention. Theoretical Contribution/Originality - The study reveals the conflicts between the South East Asian employees and the Japanese management culture in the foodservice industry. Managerial Implication in the South East Asian context - This study contributes to the organisational and human resource management literature by examining the direct and indirect effects of Japanese work culture on employees’ workplace stress and their turnover intention in the context of the restaurant industry. Research limitation & implications - As for the study limitation, the current study does not cover all Japanese restaurant in Malaysia as the researchers focus on the Klang Valley setting.